A meshless-based local reanalysis method for structural analysis. (November 2017) - Cheng, Zhenxing; Wang, Hu
Highlights: Two reanalysis methods are firstly extended for meshless method. A local search strategy for updating change of stiffness matrix is employed. Stain and stress formulations based on MLR are also given. For large modifications, the accuracy of result can be guaranteed. Both 2D and 3D numerical examples have been tested. Abstract: This study presents a meshless-based local reanalysis (MLR) method. The purpose of this study is to extend reanalysis methods to the Kriging interpolation meshless method due to its high efficiency. In this study, two reanalysis methods: combined approximations CA) and indirect factorization updating (IFU) methods are utilized. Considering the computational cost of meshless methods, the reanalysis method improves the efficiency of the full meshless method significantly. Compared with finite element method (FEM) based reanalysis methods, the main superiority of meshless-based reanalysis method is to break the limitation of mesh connection. The meshless-based reanalysis is much easier to obtain the stiffness matrixK m even for solving the mesh distortion problems. However, compared with the FEM−based reanalysis method, the critical challenge is to use much more nodes in the influence domain due to high order interpolation. Therefore, a local reanalysis method which only needs to calculate the local stiffness matrix in the influence domain is suggested to improve the efficiency further. Several typical numerical examples are tested and the performance of the suggested method is verified.